2016
DOI: 10.1007/s00240-016-0875-8
|View full text |Cite
|
Sign up to set email alerts
|

Stone volume is best predictor of operative time required in retrograde intrarenal surgery for renal calculi: implications for surgical planning and quality improvement

Abstract: Retrograde intrarenal surgery (RIRS) is highly successful at eliminating renal stones of various sizes and compositions. As urologists are taking on more complex procedures using RIRS, this has led to an increase in operative (OR) times. Our objective was to determine the best predictor of OR time in patients undergoing RIRS. We retrospectively reviewed the records of patients undergoing unilateral RIRS for solitary stones over a 10 year time span. Stones were fragmented and actively extracted using a basket. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 18 publications
5
31
0
1
Order By: Relevance
“… 14 15 Sorokin et al reported that increased postoperative complications were associated with the prolonged operating time. 16 Qiao et al reported similar findings on assessing 956 paediatric cases with CCM, in which all the patients had undergone complete cyst excision and Roux-en-Y hepaticojejunostomy. 11 The mean operating time in the said study was 3.52 hours (range 2.21–5.75 hours).…”
Section: Discussionmentioning
confidence: 64%
“… 14 15 Sorokin et al reported that increased postoperative complications were associated with the prolonged operating time. 16 Qiao et al reported similar findings on assessing 956 paediatric cases with CCM, in which all the patients had undergone complete cyst excision and Roux-en-Y hepaticojejunostomy. 11 The mean operating time in the said study was 3.52 hours (range 2.21–5.75 hours).…”
Section: Discussionmentioning
confidence: 64%
“…Whilst URS is well known to be a safe and effective way of treating renal and ureteral stones, longer operative times are associated with an increased risk of fever, bleeding, and ureteral perforation [17,27]. This could be explained by larger stone volume and complex stones [34] demanding a more difficult and lengthy procedures [35]. Ito et al examined operative times of 407 procedures, reviewing the total operative time and subdividing this into times before and after fragmentation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although the guidelines maintain this accustomed inaccuracy; a few previous studies used a volumetric measurement to evaluate the kidney stone. 26 Ito et al studied that larger stone volume prolonged the operative time. 27 Another research of the same group mentioned that stone volume is independent predictors of SFR.…”
Section: Discussionmentioning
confidence: 99%